Violence and belonging : the quest for identity in post-colonial Africa - Broch-Due, Vigdis (Routledge, 2005)
Modernisation in Africa has created new freedoms but also new problems. Multiparty democracy, privitisation and structural change have not always created stable and prosperous communities as hoped, and violence continues to be endemic in amny areas of African life - from civil war and political strife to urban, class, ethnic and gender violence. Violence and Belonging explores the crucial, formative role of violence in shaping people's ideas of who they are in uncertain postcolonial contexts. Focusing on fieldwork from across the continent, it asks how everyday violence ties in with wider poli.